Requirements and Regulation of Prefabricated Substation in Compliance with IEC 62271- 202:2022 Standard. - Hasan, Md Tarek (My University, 2024)
With the rising demand for electricity and flexible grid integration, the usage of prefabricated substations is increasing. It also minimizes project duration and cost due to its modular design and transportable capability. Although it offers several benefits, the manufacturers face many challenges in installing this prefabricated substation. Following local building codes is one of the major challenges when installing the prefabricated substation. Additionally, selecting proper materials for the structure, choosing appropriate electrical equipment, conducting testing of that equipment, and finally, safely operating this substation need to be considered. This thesis is prepared for an electrical grid integration company located in Vaasa, Finland. The primary goal of this thesis is to minimize the building code for installing prefabricated substations. This company can consider this substation building as a product by eliminating the building code for prefabricated substations and installing similar substations at different locations. The International Electrotechnical Commission (IEC), an international standard provider authority, provided the requirements for installing prefabricated substations. IEC 62271-202:2022 defines the system details, service conditions, ratings, characteristics, de-sign and construction of the prefabricated substation. This thesis investigated the requirements for different prefabricated substation elements according to the specific IEC standard. Appendix 1 will help this grid integration company to select the locations where they can install prefabricated substations without following the building code and choosing the proper electrical and structural components of the prefabricated substation. To consider prefabricated substations as a product (PSaaP), a Requirement Breakdown Structure (RBS) method has been proposed additionally to mitigate building code in complying with IEC 62271-202:2022. According to the IEC 62271-202:2022 standard, different kinds of type tests have been suggested so that this manufacturer can conduct mandatory type tests and avoid unnecessary type tests. Considering the environmental and fire safety issues, Air Insulated Switchgear (AIS) has been studied in this thesis, including its limitations. Moreover, according to the IEC standard and literature, this thesis has proposed some techniques to mitigate indoor pollution of prefabricated substations. The findings of this thesis will help the grid integration company to minimize building code in particular locations, select the proper equipment, conduct essential type tests, and mitigate indoor pollution. Therefore, it provides comprehensive guidelines and emphasizes the reliability and flexibility of the prefabricated substation from a manufacturing and installation perspective.
Keywords: electric substations; electrical engineering; IEC standards; prefabricated construction; electrical installations; electrical devices; fi=Sähkötekniikka|en=Electrical Engineering|; Master´s Programme in Smart Energy